Extracorporeal membrane oxygenation in a child with traumatic ventricular septal defect - Jennifer Y. Lam; David J. Patton; Meagan E. Mahoney; Steven R. Lopushinsky (Elsevier, 2018)
Traumatic ventricular septal defect is an uncommon event following blunt thoracic trauma. Within the pediatric trauma literature, extracorporeal membrane oxygenation is most commonly used for secondary acute respiratory distress syndrome. We present the first account of rescue extracorporeal membrane oxygenation to allow for safe transport and access to definitive operative repair in the setting of blunt cardiac injury.